PENERAPAN SISTEM DARING TERPADU DALAM PROSES PENGAJUAN GUGATAN PERDATA DI PENGADILAN DALAM UPAYA PENINGKATAN PELAYANAN PUBLIK - Lanny Lasmana (Faculty of Law, Maranatha Christian University, 2018)
Each person has different means to handle and to settle disputes. Dispute settlement can be conducted through various means, among others non-litigation and litigation. Non-litigation is conducted through the method of negotiation, mediation and consiliation, while litigation is conducted by going through the lane of civil lawsuit to the court. A dispute settlement process through the lane of civil lawsuit to the court requires a long process. Conventionally, civil lawsuit is submitted by the plaintiff against the defendant through the Chairperson of the Court at the domicile of the defendant. However, in the development, with the increase of cases submitted and registered with courts has led to long processes of lawsuit registration. Therefore, a breakthrough is needed for the registration processes of civil lawsuits at the courts to make registration more effective and efficient. On-line lawsuit registration could become a way out.This research is conducted by using the normative juridical method, supported by the sociological juridical method to complement it. The data used are secondary data consisting of primary, secondary and tertiary legal materials. While primary data are used as supporting data.The progress in technology and information opens the possibility to reduce and to optimize the integration of several functions, particularly the functions of the court registrar into one function. For instance, the receipt of dossiers of civil lawsuits can be conducted by online means, such is also with the registration of civil lawsuits. All those could be conducted without the need of meeting with the court registrar, dossier completion could be done online by by means of marking list of necessary matters (checklist) so that work efficiency can be achieved starting with the processof examination, summons, examination, and the making of minutes.